Neutrality as a strategy of national security - Цебенко, Олег; Шимчук, Олександр; Tsebenko, Oleh; Shymchuk, Oleksandr (Lviv Politechnic Publishing House, 2017)
Досліджено нейтралітет як один з основних державних стратегій. Проаналізовано основні теоретичні та методологічні підходи дослідження проблеми нейтралітету, вивчено різноманітні дефініції цього поняття та виявлено основні ознаки нейтралітету держави. Досліджено історичну еволюцію становлення стратегії нейтралітету у міжнародних відносинах. Виокремлено погляди зарубіжних та вітчизняних вчених на стратегію нейтралітету держави. Визначено основні держави, що дотримуються політики нейтралітету, а також Україна, яка колись дотримувалась цієї стратегії.

The complex study of the state neutrality strategy is done. The theoretical and methodological basis of neutrality strategy is analyzed, the problem of definition this phenomenon is investigated, the main aspects of neutrality strategy tendencies are clarified. When Ukraine gained independence after the dissolution of the USSR, the new country declared an intention to become a permanently neutral state that does not participate in military blocs. The concepts of neutrality have been considered an effective means of pursuing foreign policy and ensuring a national security of the new state. This research undertakes an investigation of the transformation of the concept of neutrality under the conditions of the dynamic process of globalization in the modern international relations. It aims to examine the changes in the priorities in the foreign policy of the states that declared a permanently neutral and non-aligned status. The methods are used to identify scholarly theories that view neutrality as a security strategy. It was pointed out that neutrality as a security strategy had become most significant, during the Cold War. In this respect, the end of bipolarity brought uncertainty and ambivalence in the perception of the notion of neutrality. On the one hand, the rationale for neutrality in the age of globalization seemed to disappear; on the other hand, the neutral states had increased their activities in new areas and become newly involved in international politics. The hypothesis of the thesis was that neutrality remained to be an effective tool in the conceptual formation and implementation of the foreign policy of the states under the conditions of the dynamic development of the modern international relations. However, it was pointed out that the success of neutrality depended on a state’s ability to maintain a credibility of the very status, taking into account a geopolitical location of the state and a positive perception of such a status by the potential belligerents, alliances, blocs, and the leading actors of the international relations, on the whole. Neutrality as a status of the state that resists participation in war actions with the other states remains to be a vital concept in the international politics. Its evolution under the conditions of the bipolar system of international relations led to the emergence of the politics of non-alignment, which is considered unilaterally declared status that does not necessarily need to be internationally-legally stipulated and that provides a state with somewhat broader space for action, only via limiting its participation in military blocs. Furthermore, with the emergence of new sectors of security and homogeneity of the world in the age of globalization, the concept of neutrality did not lose its meaning. The European neutrals proved that in the conditions of the formation of the multipolar system of international relations and the new system of European security, neutrality may become one of the indispensable elements for their proper functioning.
Нейтралітет як стратегія національної безпеки
Keywords: Україна; нейтралітет; неприєднання; безпека; глобалізація; авторитет; Ukraine; neutrality; non-alignment; security; globalization; credibility; 327.8